A narrative case study of an older disabled Muslim woman during the COVID-19 pandemic in the UK - Alnamnakani, Amani (Frontiers in Sociology, 2024)
This paper explores the experiences and perceptions of Zora, an older Muslim woman living with a disability in the UK. Older disabled Muslim women in the UK often face multiple discriminations based on disability, age, gender, religious, and racial grounds and this has arguably been intensified by the COVID-19 pandemic. Drawing on multiple narrative interviews with Zora, this paper focuses on the intersections of disability, ageing, gender, race and religion within a particular social context during the COVID-19 pandemic in the UK.The paper describes the complex ways in which Zora experienced various modes of everyday disablism which were not related to the COVID-19 virus itself, rather the consequences of the mobility restrictions associated with it. Much of the oppression and barriers she described were socially determined, both through direct discrimination, stares and prejudicial attitudes, and indirectly through stigmatisation and an embodied fear of the reaction of others in public spaces. Nevertheless, Zora did not present herself as a victim.Instead she portrayed herself in affirmative terms, as a 'brave' woman who resisted and overcame daily social challenges and movement restrictions as part of working towards creating a more accessible, inclusive and age-friendly society. One that is inhabitable for herself and other older disabled women facing an uncertain future.